Corrosion of steel reinforcements embedded in FRP wrapped concrete - Gadve, S.; Mukherjee, Abhijit; Malhotra, S. (Elsevier BV, 2009)
A large number of reinforced concrete (RC) structures that have been damaged due to corrosion of steel reinforcements are rehabilitated with fiber-reinforced polymer (FRP) composites. This paper investigates the progression of corrosion of steel in concrete after it has been treated with surface bonded FRP. Concrete cylinders with embedded steel bars are immersed in salt water and anodic current is passed through the reinforcement to initiate cracking in concrete due to accelerated corrosion of steel. Glass and carbon FRP sheets have been adhesively bonded on the cylinders. Anodic current was continued for specified times. Pull out strength, mass loss, half cell potential of the steel and cell voltage have been reported as metrics of performance of the samples. FRP wrapped samples have shown substantially higher resistance to corrosion.